PHISICAL EDUCATION QUALITY IN HIGHER EDUCATION (GYMNASIUM, 2009)
A quality service is one which fulfils a set of demands and rules according to a standard andespecially according to the internal and external client’s expectations. Reaching these goals implies also anew relationship between the service provider and the beneficiary. As a consequence, in educational systemis expected also a change regarding the improvement of the educational offer, the educational context, thequality of the human resources and the relationship between teacher and student. We might know if theeducational service we provide is a corresponding one through measurements, statistics and objective data.This allows comparisons and classifications among the educational institutions and they prove the evolutionin time also. The progress must be the main criteria for all the decisions, actions and process involved inhigher education teaching.